Avtomatizmi - kolokacije - Logar, Nataša (Jezik in slovstvo, 2023)
In our paper, we first conducted a detailed examination of Korošec‘s interpretation of automations. We then compared his definition of this linguistic phenomenon with collocations, which, like automations, involve predictable combinations of words. According to Korošec‘s theory, expressions such as “According to informed sources”, “This is John Smith, reporting from London”, and “Turn to page X” are clearly classified as automations. However, we were intrigued by whether examples like “pay attention” and “bottleneck” (referring to a narrow section of road or a situation causing delay) also fit the category of automations, despite not fulfilling the criteria of: (1) referencing the source of in-formation, (2) referring to one‘s own reporting, and (3) guiding readers through newspaper pages. After all, expressions like “pay attention” and “bottleneck” are commonly used in news reporting. Subsequently, we closely examined 18 examples of automations and potential automations, which we initially presented in the first part of our discussion. We assessed whether they were documented in two collocation dictionaries and identified additional similar instances. Our analysis revealed that both automations and potential automations can be categorized as collocations. Consequently, our critical assessment of the theory and examples of automations, the comparison between the characteristics of automations and collocations, as well as insights from dictionaries, led us to conclude that we should abandon the concept of automations altogether and instead classify predictable word combinations in journalism as collocations.
Keywords: automations; avtomatizmi; collocations; journalism; kolokacije; Korošec, Tomo; news reporting; novinarstvo; poročevalstvo; referencing; sklicevanje; Slovene; slovenščina; stilistika; stylistics